HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DENGAN KEPATUHAN KUNJUNGAN ANC DI PUSKESMAS SITIUNG 1 KAB.DHARMASRAYA - Purwati, Rati; Sukmawati, Sukmawati; Khairunisa, Khairunisa (Jurnal Doppler, 2023)
World Healt Organization (WHO) in 2017, the maternal mortality rate in the world was 810 maternal deaths per 100.000 live births per day, and maternal mortality data in ASEAN showed that Indonesia ranks second highest. According to WHO reports, 75% of maternal deaths are caused by bleeding, infection and high blood pressure in the mother during pregnancy. Danger signs of pregnancy are signs or symptoms that indicate the mother or baby she is carrying is in danger. Every pregnancy, in its development there is a risk of pregnancy complications or complications. There for antenatal care must be carried out rountinely according to standars and in an integrated manner for quality antenatal services (Mahadewi, 2016). Analytical survey research method with a cross sectional approach. Cross sectional is research conducted in a certain time. Statistical test used chi square test. Through data analysis with statistical test using chi square with 34 respondents, the results showed that half of pregnant women with low knowledge levels were 17 people (50,0%). Then most of pregnant women with obedient levels in ANC visits were 19 people (55,9%). From the test result, the p-value = 0,53 >0, 05 means that there is no relationship between knowledge of pregnant women about the danger signs of pregnancy and compliance with antenatal visits